Hazard identification, risk assessment and risk control (HIRARC) in a corrugated box manufacturer / Fraziel Barahim - Barahim, Fraziel (2010)
Packaging is one of the biggest industries in the world. It involves paper, glass,metal, flexible and plastic. The corrugated paper packaging worldwide has been growing at 3% to 4% per annum. In line with the expansion of the corrugated paper packaging manufacturing, the potential hazards to human physical and health, property and the environment posed by its operations and production activities have created an increase in awareness and brought up safety issues amongst industry, government and public. The hazard identification and risk assessment plays a role in a number of areas in the safety management, including regulatory policies and guidelines, and both operational and financial management of industrial or resource development industries for all stakeholders. In this study, the risk assessment has been conducted in a company and all the actual risks are identified and quantified based on the level of risk in the identified work areas or machineries based on previous records and assessment done. The risk assessment provides a means of identifying and quantifying the potential impacts of industrial activities on human health and the environment and used to predict the likelihood, to estimate the level of hazard and to select an appropriate course of mitigation or control measures. The high risks are reduced by improving the control measures such as reducing the exposure of certain job steps that will cause potential hazard.